Multiple Interactions Mixed Matrix Membrane Chromatography Using Anion and Cation Exchanger Resin for Whey Protein Fractionation - Chan, Fong Shiew; Nurul, Shamsinar; Nurul Izwanie, Rasli; Syed Mohd Saufi, Tuan Chik (Penerbit Universiti Teknologi Malaysia, 2015)
Membrane chromatography can overcome the limitation of packed bed chromatography in terms of high processing speed, low pressure drop and acceptable protein binding capacity. In the current study, multiple interactions mixed matrix membrane (MMM) chromatography was prepared for batch fractionation of whey protein. Lewatit CNP105 cation exchanger resin and Lewatit MP500 anion exchanger resin were mixed into two different membrane polymer solutions of ethylene vinyl alcohol (EVAL) and cellulose acetate (CA). The membranes were test to bind lactoferrin (LF)-spiked whey. The binding capacity for acidic whey proteins to the MMM follows the order of β-lactoglobulin (β-Lac) > BSA > α-lactalbumin. The binding capacity of EVAL MMM is higher than CA based MMM, more prominently for β-Lac. The average binding capacity of β-Lac in the EVAL and CA MMM are 50.827 mg β-Lac/ g MMM and 19.174 mg β-Lac /g MMM, respectively. High purity of β-Lac and LF were recovered from the MMM after the elution as shown by the SDS PAGE gel.